Vinazas de mezcal y su efecto biofertilizante en el rendimiento de hortalizas - Zelaya-Benavidez, Edwin Alfonso; Martínez-Gutiérrez, Gabino Alberto; Escamirosa-Tinoco, Cirenio; Morales, Isidro (Ecosistemas y Recursos Agropecuarios, 2022)
Mezcal vinasses are recalcitrant liquid waste with a high organic load and dissolved elements that can be used in plant nutrition. The objective work was to evaluate the toxicity of mezcal vinasse on seed germination and its biofertilizing effect on vegetable yield. Two experiments were carried out on lettuce, tomato and cucumber: 1) germination phytotoxicity test in seeds with different concentrations of vinasse (2.5, 5, 10, 20, 40, 80 and 100%); and 2) The biofertilizing effect of the combinations of 100-0, 80-20, 40-60 and 20-80% vinasse and Steiner nutrient solution was evaluated, and 100% of the nutrient solution as a control. A completely randomized design was used in both experiments. The 2.5% concentration of mezcal vinasse was toxic to lettuce seeds and greater than 10% inhibited their germination. For tomato seeds the 20% was toxic, while in cucumber seeds it caused hormesis. The 80% concentration of vinasses inhibited germination in tomato seeds. The combination: 40 + 60% vinasse and nutrient solution applied in the nutrition of lettuce and tomato, reached the maximum values of all the variables evaluated. In cucumber, the yield decreased linearly with increasing the vinasse percentage as a supplement to the nutrient solution.